A Fuzzy-based Methodology for Landslide Susceptibility Mapping. (10th June 2016) - Barrile, Vincenzo; Cirianni, Francis; Leonardi, Giovanni; Palamara, Rocco
Abstract: The present paper proposes a new methodology to characterize the landslide susceptibility of Reggio Calabria territory. The values obtained were classified into five categories: very low, low, medium, high and very high, and were than exported into GIS environment to produce a landslide susceptibility map. The principal objective of the proposed study is to identify the sections of the road network exposed to landslide hazards starting from the susceptibility map. To this aim, a fuzzy system was designed with 2 input, 15 rules "if-then" and 1 output representing the "level of attention" for the considered transport infrastructure, being a higher value of attention level correspondent to a higher landslide hazard.